Unsteady free convection flow past a semi-infinite vertical plate with constant heat flux in water based nanofluids - Narahari, M. (Institute of Physics Publishing, 2018)
The unsteady free convective flow of nanofluids past a semi-infinite vertical plate with uniform heat flux has been investigated numerically. An implicit finite difference technique of Crank-Nicolson scheme has been employed to solve the governing partial differential equations. Five different types of water based nanofluids containing Cu, Ag, Al2O3, CuO and TiO2 nanoparticles are considered to study the fluid flow characteristics with various time and solid volume fraction parameters. It is found that the local as well as the average Nusselt number for nanofluids is higher than the pure fluid (water). The local skin-friction is higher for pure fluid as compared to the nanofluids. The present numerical results obtained for local Nusselt number are validated with the previously published correlation results for a limiting case and it is found that the results are in good agreement. Â© Published under licence by IOP Publishing Ltd.